Model for web system development and management -Najran University as a model: نموذج جديد لتطوير وإدارة موقع الويب في جامعة نجران - Fouad Shabib Al Khasawneh - Mohammed Abdul Karim Aqla Al Arqan (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2018)
With the rapid development of software and applications, the World Wide Web has become an appropriate environment for software and application development because these applications deployed on websites continuously. There is a need to update websites continuously. Most organizations update their data without having developed according to the appropriate methods and quality standards. Website development includes multiple areas, such as computer science, hypertext, graphic design, document management and software engineering. Therefore, we need a team having knowledge in all areas of website development. As a result, the development of Web applications has become more complex and challenging to a large number of organizations because there are various methods and techniques for developing websites and the lack of acceptable methodology or procedures for the development of websites. Therefore, there is a need to adopt integrated methodology for developing websites. This research proposes a new model for the development of all types of web systems called the Object Relationships Model for Web System Management (ORMFWSM). The model consists of ten interrelated phases and each phase consists of a set of activities that should be checked. If the new model was applied at Najran University website, it would improve the methods of development and management for Najran University website and it is going to be an adequate model to develop all types of web-based systems.